E-Encyclopedia for Biology Education: Design, Development, and Evaluation of an Innovative Learning Resource - Suraida; Saputra, Jihan; Salahuddin; Syefrinando, Boby; Susanti, Try (Yayasan Nurul Yakin Bunga Tanjung, 2025)
Understanding laboratory equipment is a fundamental competency in science education. However, students often face difficulties in mastering laboratory tools due to the lack of practical and reliable learning resources. Dependence on invalid sources negatively affects the quality of practicum and research. This study aims to develop and evaluate the feasibility of a digital encyclopedia on laboratory equipment as a learning resource to enhance the effectiveness of science learning. The research employed a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. The Define stage involved needs analysis through surveys and interviews, curriculum analysis, student characteristics analysis, and formulation of learning objectives. The Design stage focused on creating a product prototype. The product was validated by four experts (a subject matter expert, a media expert, a language expert, and an instructional design expert). Practicality testing involved 28 students and 4 lecturers from the Biology Education study program. The validation results showed scores of 93% for language, 93.2% for content, and 95% for media, indicating that the digital encyclopedia is very feasible for use. Practicality tests resulted in a score of 96.2% from students and 88.33% from lecturers, indicating that the product is very practical, engaging, and effective in supporting independent learning. The final results conclude that the digital encyclopedia is both valid and practical as a learning resource. The study recommends further development with broader content coverage and the integration of Augmented Reality (AR) technology to enhance interactivity.